2004
DOI: 10.1002/anie.200460955
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Reactivity of a Nickel N‐Heterocyclic Carbene Complex: tert‐Butyl Group Cleavage and Silicone Grease Activation

Abstract: Reaction lubrication? The reaction between [Ni(1,5‐cod)2] (cod=cyclooctadiene) and 1,3‐bis‐tert‐butylimidazol‐2‐ylidene in the presence of silicone grease affords the siloxane bridged dimer [{Ni[C(NtBuCH)2][O(Me2SiOSiMe2)‐μ‐O]}2]. In a greaseless apparatus, the same reaction yields the dimer 1 (see structure), via two structurally characterized intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
75
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(87 citation statements)
references
References 34 publications
12
75
0
Order By: Relevance
“…[2] A number of groups have observed that N-alkyl and N-aryl-substituted NHCs are prone to both CÀH and CÀN activation of the peripheral organic substituents within the coordination sphere of transition-metal centers. [3,4] Herein we report that the imidazol-2-ylidene ring is prone to reductive ring opening in the presence of reactive hydride compounds; observations that may be of particular relevance to hydride poisoning of NHC-based catalysts.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…[2] A number of groups have observed that N-alkyl and N-aryl-substituted NHCs are prone to both CÀH and CÀN activation of the peripheral organic substituents within the coordination sphere of transition-metal centers. [3,4] Herein we report that the imidazol-2-ylidene ring is prone to reductive ring opening in the presence of reactive hydride compounds; observations that may be of particular relevance to hydride poisoning of NHC-based catalysts.…”
mentioning
confidence: 96%
“…Although generally noted for their stability, particularly under catalytic conditions, NHC complexes are susceptible to degradation by a variety of C À H, C À C, and C À N bond-activation reactions at peripheral and/or extracyclic positions. [2][3][4] The reaction to produce compound 3 is unprecedented, however, as it involves complete disruption of the s and p systems of the imidazolylidene framework.…”
mentioning
confidence: 99%
“…Moreover, PDMS appears to be suitable as the protecting media for the preparation of latetransition-metal complexes, since there are only very few reported cases where complexes are known to react with PDMS. [25] In all cases, the silicone matrix was easily removed by washing the resulting complexes with pentane.…”
mentioning
confidence: 99%
“…The question presents itself, what is the driving force for the realisation of structure type A or B. In the structurally determined homoleptic bis-carbene complexes of the zero valent metals nickel, palladium and platinum, only structure type B is found [35][36][37][38][39][40][41][42][43]. The carbene ligands in these complexes have sterically demanding substituents at the nitrogen atom (mesityl, tert-butyl, adamantyl) [38][39][40][41][42][43], which raises the suspicion that the tilting of the carbene ligands may have steric reasons.…”
Section: Trans-bis-carbene Complexesmentioning
confidence: 98%